Incidence of Eimeria spp. in Fat-Tailed Sheep Breed in Malang, Indonesia - Nurdianti, Nurdianti; Yunus, Muchammad; Mufasirin, Mufasirin (Universitas Airlangga, 2023)
Coccidiosis caused by Eimeria spp. is a parasitic disease that affects various animal species, including sheep. This study aimed to detect Eimeria spp. and the degree of infection in the fat-tailed sheep breed in Malang. This study used fecal samples from 62 fat-tailed sheep. Detection of Eimeria spp. was performed by using the flotation method and then observed the morphology of the oocysts found in the fecal samples of fat-tailed sheep. The positive sample was followed by the McMaster test to calculate oocysts per gram (OPG). The results showed that 20 (32%) samples were positively infected by Eimeria spp. with the degree of infection in the severe category.